Tm, Ho:KY(WO4)2 planar waveguide laser. (29th July 2016) - Ruiz Madroñero, C V; Mateos, X; Loiko, P; Yumashev, K; Petrov, V; Griebner, U; Aguiló, M; Díaz, F
Abstract: A lattice-matched, 5 at.% Tm, 0.5 at.% Ho-codoped, 5.77 µ m-thick KY0.58 Gd0.22 Lu0.20 (WO4 )2 active layer with optimized refractive index contrast is grown by liquid phase epitaxy on the (3 1 0) face of pure KY(WO4 )2 substrate. Laser operation at 2051 nm ( 5 I7 → 5 I8 transition of the Ho 3+ ion) is demonstrated with this waveguide pumped at 794 nm. The maximum continuous wave output power amounts to 1.9 mW at 2051 nm corresponding to a slope efficiency of 10.5%. The laser threshold is as low as 1.5 mW of absorbed pump power. The developed structure is promising for single-transverse-mode channel holmium waveguide lasers. Laser operation in 3 at.% Tm-singly doped 4.41 µ m thick layer grown on the (3 1 0)-oriented substrate is also demonstrated at 1841 nm with a slope efficiency of 31%.